Relatório de Estágio Profissional "PERCEÇÃO DA IMPORTÂNCIA DA DISCIPLINA DE EDUCAÇÃO FÍSICA NO CURRÍCULO ESCOLAR" - André Manuel de Sousa Fernandes (2017)
This work aims to present all the work developed by me during the professional internship in a reflexive and critical way of my formative experience. Thus, I present my experiences of Internship, achievements, difficulties and problems, which I encountered during this year. The Professional Internship took place at the Basic and Secondary School of Velas, accompanied by a Cooperating Teacher and a Faculty Advisor. This report is organized into 6 chapters: (1) Introduction, where the report is framed, mentioning its objectives, brief contextualization and organization; (2) Personal Dimension, narrating a course of life, having some significant personal passages, such as passion for the chosen path, sport; (3) Institutional Framework, with expectations and professional experiences being reported as a trainee teacher, understanding of the importance of the school in the county in which it is inserted, as presentation of the composition of the Department of Physical, Artistic and Technological Education; (4) Operational Environment and its realization; (5) for the "Research Study" where we aimed to investigate students 'and teachers' perceptions regarding the importance of Physical Education in the school curriculum as well as to understand the influence of Physical Education in the access to higher education; (6) Final Consideration, where a synthesis of the contribution of this work as a teacher is made as well as their future perspectives.